Refrigeration technology - Ze-Zhao, Hua (Science Press Alpha Science, 2012)
Introduces the fundamentals of refrigeration technology, the development of the technology over the years and its status. This book includes the introduction of the category, applications, history and development of refrigeration and the academic organizations and journals in this field